The early career researcher's toolkit: translating tissue engineering, regenerative medicine and cell therapy products. (November 2015) - Rafiq, Qasim A; Ortega, Ilida; Jenkins, Stuart I; Wilson, Samantha L; Patel, Asha K; Barnes, Amanda L; Adams, Christopher F; Delcassian, Derfogail; Smith, David
Although the importance of translation for the development of tissue engineering, regenerative medicine and cell-based therapies is widely recognized, the process of translation is less well understood. This is particularly the case among some early career researchers who may not appreciate the intricacies of translational research or make decisions early in development which later hinders effective translation. Based on our own research and experiences as early career researchers involved in tissue engineering and regenerative medicine translation, we discuss common pitfalls associated with translational research, providing practical solutions and important considerations which will aid process and product development. Suggestions range from effective project management, consideration of key manufacturing, clinical and regulatory matters and means of exploiting research for successful commercialization.